Antioxidant diet supplementation influences blood iron status in endurance athletes - Aguilo, A.; Tauler, P.; Fuentespina, E.; Villa, G.; Cordova, A.; Tur, J. A.; Pons, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
Objective: The aim of this work was to check the effects of antioxidant supplementation (vitamins E and C, and b-carotene) on the basal iron status of athletes prior to and following their training and competition season (3 months). Design: Eighteen amateur trained male athletes were randomly distributed in 2 groups: placebo (lactose) and antioxidant supplemented (vitamin E, 500 mg/d; vitamin C, 1 g/d; and b-carotene, 30 mg/d). The study was double blind. Hematological parameters, dietary intake, physical activity intensity, antioxidant status (GSH/GSSG ratio), and basal iron status (serum iron, transferrin, ferritin, and iron saturation index) were determined before and after the intervention trials. Results: Exercise decreased antioxidant defenses in the placebo group but not in the antioxidant-supplemented group. No changes were found in the number of erythrocytes, hematocrit, or hemoglobin concentration, or in values of serum iron parameters, after taking the antioxidant cocktail for 3 months, in spite of the exercise completed. The placebo group showed a high oxidative stress index, and decreases in serum iron (24%) and iron saturation index (28%), which can neither be attributed to aspects of the athletes' usual diet, nor to hemoconcentration. Conclusions: Antioxidant supplementation prevents the decrease of serum iron and the iron saturation index, and a link between iron metabolism and oxidative stress may also be suggested.